A frameshift variant in the COL5A1 gene in a cat with Ehlers‐Danlos syndrome. (23rd September 2018) - Spycher, M.; Bauer, A.; Jagannathan, V.; Frizzi, M.; De Lucia, M.; Leeb, T.
Summary: Ehlers‐Danlos syndrome (EDS) is a group of heritable connective tissue disorders caused by defective collagen synthesis or incorrect assembly of the collagen triple helical structure. EDS is characterised by joint hypermobility, skin hyperextensibility, abnormal scarring, poor wound healing and tissue friability. Human EDS may be caused by variants in several different genes including COL5A1, which encodes the collagen type V alpha 1 chain. For the present study we investigated a 1.5‐year‐old, spayed female, domestic shorthair cat with EDS. The affected cat showed multiple recurrent skin tears, hyperextensibility of the skin and joint abnormalities. We obtained whole genome sequencing data from the affected cat and searched for variants in candidate genes known to cause EDS. We detected a heterozygous single base‐pair deletion in exon 43 of the COL5A1 gene, namely c.3420delG. The deletion was predicted to result in a frameshift and premature stop codon: p.(Leu1141SerfsTer134). Sanger sequencing confirmed that the variant was present in the affected cat and absent from 103 unaffected cats from different breeds. The variant was also absent from a Burmese cat with EDS. Based on knowledge about the functional impact of COL5A1 variants in other species, COL5A1 :c.3420delG represents a compelling candidate causative variant for the observed EDS in the affected cat.